TIME AND SPACE STRUCTURE OF ISRA' MI'RAJ IN THE PERSPECTIVE OF TAFSIR, RELATIVITY THEORY AND ANNIHILATION THEORY - Dina Sabella; Fauzan Saleh; Emma Rahmawati (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
The first verse of Surah Al-Isra‘ reveals the most improbable event in prophetic history that is most difficult for the mind to understand and accept, namely the Isra’ and Mi'raj events of Prophet Muhammad SAW. Traditional transportation at that time did not allow for traveling to and from the Grand Mosque in Makkah and the Aqsa Mosque in Palestine, which is about 1,500 km away. However, how do the Mufasir and the viewpoint of science (which prioritizes logic) view this event? This research method uses a qualitative approach, with the type of literature study research. Data collection techniques include literature searches from books, scientific articles, and other relevant sources that discuss Isra' Mi'raj according to Al-Razi's opinion in Tafsir Mafatih al-Ghayb and Albert Einstein's Theory of Relativity and Annihilation. The data analysis was carried out using content analysis techniques, in which researchers identified the main topics that emerged from the collected sources. This research found that Allah SWT made the Isra' Mi'raj event of Prophet Muhammad SAW and was not bound by time and space in order to reach Sidratul Muntaha. Isra' Mi'raj emphasizes faith reasoning more. Isra' Mi'raj only happened once in history, and this is a miracle given to the Prophet Muhammad SAW from what was impossible to be possible because Allah's power is limitless.